2009
DOI: 10.1080/07399330902785133
|View full text |Cite
|
Sign up to set email alerts
|

“It Is Always on My Mind”: Women's Experiences of Their Bodies When Living With Hirsutism

Abstract: Many women suffer from excessive hair growth, often in combination with polycystic ovarian syndrome (PCOS). It is unclear how hirsutism influences such women's experiences of their bodies. Our aim is to describe and interpret women's experiences of their bodies when living with hirsutism. Interviews were conducted with 10 women with hirsutism. We used a qualitative latent content analysis. Four closely intertwined themes were disclosed: the body was experienced as a yoke, a freak, a disgrace, and as a prison. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 30 publications
7
33
1
2
Order By: Relevance
“…The area less affected was work and school. These results further strengthen what has been found in a previous qualitative article by Ekbäck et al [8], where women were working, but did not participate in activities with work mates outside their work, in case they risked revealing their hairiness because of the embarrassment and guilt they felt over their situation. This is also in line with the higher levels of ‘social fears' that Sonino et al [2] reported among women with hirsutism compared to women without hirsutism.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The area less affected was work and school. These results further strengthen what has been found in a previous qualitative article by Ekbäck et al [8], where women were working, but did not participate in activities with work mates outside their work, in case they risked revealing their hairiness because of the embarrassment and guilt they felt over their situation. This is also in line with the higher levels of ‘social fears' that Sonino et al [2] reported among women with hirsutism compared to women without hirsutism.…”
Section: Discussionsupporting
confidence: 79%
“…The areas most affected are the face and the lower abdomen [6]. Hair in the face is considered most troublesome, can preoccupy the women's minds [7,8] and can be experienced as a betrayal of womanhood [9]. In addition the social norm of femininity today includes to be totally free of body hair [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the social norm of femininity, i.e., being hairless [7,8] and thin [9] are ideals far away from living with hirsutism. This discrepancy makes the women feel abnormal and ashamed of themselves [10]. In a previous study, we also found that women with hirsutism often felt disappointed and not listened to by health care personnel [10].…”
Section: Introductionmentioning
confidence: 81%
“…As shown in a qualitative study, hirsute women feel "slaves of their own body" and describe this condition as a "prison" [ 16 ]. Moreover, looking in the mirror very often could represent an obsessive-compulsive behavior [ 17 ].…”
Section: Hirsutismmentioning
confidence: 98%